Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1093/ejcts/ezu102
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid multistep approach to mega-aortic syndrome: the Lupiae technique

Abstract: These results evidence that the Lupiae technique is a safe and effective option for the treatment of patients with MAS, achieving the complete exclusion of thoraco-abdominal aneurysms and of the residual false lumen in patients with acute aortic dissections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Hybrid aortic repair using an endovascular technique has emerged as an alternative to the conventional twostage elephant trunk technique. 3,10) Recently, Roselli et al reported that the high rate of endoleaks for the endovascular completion in patients who have already undergone conventional elephant trunk technique. 10) This reason is possibly due to the free-floating design of the original version of the elephant trunk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybrid aortic repair using an endovascular technique has emerged as an alternative to the conventional twostage elephant trunk technique. 3,10) Recently, Roselli et al reported that the high rate of endoleaks for the endovascular completion in patients who have already undergone conventional elephant trunk technique. 10) This reason is possibly due to the free-floating design of the original version of the elephant trunk.…”
Section: Discussionmentioning
confidence: 99%
“…Giant cell aortitis (GCA) is an uncommon cause of thoracic aortic aneurysms, which often involve the aorta from the aortic root through the arch, extending to the thoracoabdominal aorta, the so-called mega-aortic syndrome (MAS). [1][2][3] We performed a two-stage hybrid repair, combining open and endovascular techniques, to treat MAS due to GCA in a heart failure patient with severe aortic regurgitation.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid aortic repair with antegrade supra-aortic and renovisceral debranching from ascending aorta and 94% at 28 months, 6 and 8 years, have been reported with this procedure (6)(7)(8)(9). A three-year estimated survival rate of 83%; freedom of type I endoleak and reintervention of 100% and 78%, respectively, have been also reported (10).…”
Section: Introductionmentioning
confidence: 86%
“…We previously proposed a MAS classification (3,4) according to the distal extent of the aneurysms, with MAS type I aneurysms terminating above the coeliac trunk, MAS type II aneurysms terminating between coeliac trunk and the renal arteries (RA), and MAS type III aneurysms terminating below the RA (Figure 1). The focus of this report is on MAS type III patients.…”
Section: Introductionmentioning
confidence: 99%
“…This proximal landing zone can be used to complete the repair of a residual descending aorta aneurysm with a TEVAR. Results of this procedure for aortic dissections and thoracic aneurysms are well established (3,4,6).…”
Section: Introductionmentioning
confidence: 99%